Effect of mid-luteal phase GnRH agonist on frozen-thawed embryo transfers during natural menstrual cycles: a randomised clinical pilot study. (1st December 2016) - Seikkula, Jaana; Anttila, Leena; Polo-Kantola, Päivi; Bloigu, Risto; Engblom, Janne; Tinkanen, Helena; Jokimaa, Varpu
Abstract: This prospective randomised crossover study evaluated the effect of mid-luteal single-dose gonadotropin-releasing hormone agonist (triptoreline) on pregnancy outcomes in natural-cycle frozen embryo transfers (FETs). Ninety-eight women were randomised to receive either standard luteal support with vaginal micronised progesterone or an additional single dose of 0.1 mg triptoreline at the time of implantation. The intervention group was composed of 65 FET cycles and the control group of 62 cycles. In the intervention group, there were more positive pregnancy tests, clinical pregnancies and live births, but the differences did not reach statistical significance. The mean beta human chorionic gonadotropin (β-hCG) concentration of singleton pregnancies was significantly lower in the intervention group compared to the control group ( p  = 0.048). No difference was detected in the median birth weight of the newborns.